Factors Affecting the Incidence of Diarrhea in Toddlers in Indonesia: A Review - Anjelin Rizky Fadilah; Salsabila Rosya (Journal of Epidemiology and Health Science, 2025)
Background: Diarrhea is a gastrointestinal disease characterized by increased stool frequency (more than three times daily) with watery consistency, primarily affecting toddlers due to their immature immune systems. It remains a leading cause of morbidity and mortality in children under five, especially in areas with inadequate sanitation and hygiene practices. Transmission often occurs through contaminated food or water and poor hygiene behaviors. Several factors contribute to diarrhea incidence, including environmental sanitation, maternal knowledge, socio-economic status, nutritional intake, and exclusive breastfeeding practices. Other risk factors include improper waste disposal, limited access to clean water, and suboptimal health behavior such as lack of handwashing. Objective: This study aims to identify and describe the factors associated with diarrhea incidence in toddlers through a literature review. Methods: A systematic literature review was conducted using journal articles published between 2021 and 2025. The articles were obtained through Google Scholar using Indonesian-language keywords related to diarrhea in children. Results: The findings indicate that environmental sanitation, maternal knowledge, socio-economic conditions, and child feeding practices are dominant factors associated with diarrhea. Access to clean water, use of family latrines, waste management, exclusive breastfeeding, and handwashing practices are key protective factors. Conclusion: The incidence of diarrhea in toddlers is influenced by a combination of environmental, behavioral, and socio-economic factors. Strengthening maternal education and improving sanitation facilities are essential strategies for diarrhea prevention in young children. Keywords: Diarrhea, Toddlers, Risk Factors, Sanitation, Maternal Knowledge, Socio-economic Conditions, Exclusive Breastfeeding.